Fluid Management for Critically Ill Patients, Based on the ROSE Concept, an Old Method but Effective Enough - Agustina, Ayu Yesi; Wisudarti, Calcarina Fitriani Retno; Widodo, Untung (Journal of Anaesthesia and Pain, 2024)
Fluid therapy is one of the most essential things in managing critical patients, such as ICU patients. Although it seems simple, this is difficult to do in this group of patients. The fluid needs of ICU patients vary according to the course of the disease. Therefore, fluids must be given according to individual needs, and each phase of the disease must be reassessed. To support this, there is a conceptual model that explains fluid administration based on the phases of the disease that the patient is going through. The ROSE concept (resuscitation, optimization, stabilization, and evacuation) describes the phases of a patient's illness and how fluids should be administered. In the resuscitation phase, the goal is lifesaving and is achieved by positive fluid balance. In the optimization phase, fluid balance is neutral and aims to save organs. In the stabilization phase, the fluid balance has started to move in a negative direction and aims to support the organs. Finally, in the evacuation phase, fluid balance is negative and organ repair has occurred. By implementing this model, it is hoped that ICU patients will have better outcomes